Choice of the sizes of samples in case of determination of heat diffusivity of optical quartz glass by method of laser pulse; European Physical Journal Web of Conferences (EPJ Web of Conferences); Vol. 82 : Thermophysical Basis of Energy Technologies - Kats M. D. Mark Davydovich (2015, 2015)
Title screen